Association of Hepatic Steatosis With Subclinical Atherosclerosis: Systematic Review and Meta‐Analysis. Issue 8 (6th July 2018) - Kapuria, Devika; Takyar, Varun K.; Etzion, Ohad; Surana, Pallavi; O'Keefe, James H.; Koh, Christopher
Abstract : Non alcoholic fatty liver disease is associated with metabolic syndrome, as well as coronary artery disease. This meta‐analysis examines the relationship of NAFLD with subclinical atherosclerosis. Abstract : Nonalcoholic fatty liver disease (NAFLD) is becoming common in the United States and throughout the world and can progress to cirrhosis, hepatocellular carcinoma, and death. There is a strong association between coronary artery disease and NAFLD due to common risk factors, such as metabolic syndrome, obesity, and diabetes mellitus. Subclinical atherosclerosis, defined as coronary artery calcification in asymptomatic patients, has been shown to have a higher incidence in patients with NAFLD. We performed a meta‐analysis to examine the association of NAFLD with subclinical atherosclerosis measured by coronary artery calcium (CAC) scoring. Data were extracted from 12 studies selected using a predefined search strategy. NAFLD was diagnosed by abdominal ultrasound or computed tomography scans. The rate of coronary artery calcification was analyzed using random effects models, and publication bias was assessed using Egger's regression test. A total of 42, 410 subjects were assessed, including 16, 883 patients with NAFLD. Mean CAC score was significantly higher in subjects with NAFLD compared to those without NAFLD (odds ratio with random effects model, 1.64; 95% confidence inteval, 1.42‐1.89). This association remained significant through subgroup analyses for studies with >1, 000 subjects and a higher CAC score cutoff of >100. Higher aspartate aminotransferase levels were also associated with increased subclinical atherosclerosis (mean difference 1.77; 95% confidence interval, 1.19‐2.34). Conclusion: There is an increased prevalence of subclinical atherosclerosis in patients with NAFLD, where subclinical atherosclerosis is defined using a "real world" clinical biomarker, namely the CAC score. Prospective studies are needed to establish a causative link between NAFLD and coronary artery disease. ( Hepatology Communications 2018; 00:000‐000)